Uji Beda Jenis Umpan Dalam Penggunaan Fly Trap Warna Kuning - Dimas Hanif Abdi Rahman; Alby Fadlirahman; Chindy Sanjaya; Devi Meitha Sofiani; Emilda Silviana; Michelle Margareth; Nur Wahdini; Ramadhani Putri Nurislam; Syarif Bagus Santoso; Andi Daramusseng (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Flies are the main nuisance insects and mechanical vectors which in their bodies can carry various diseases such as diarrhea, myiasis, helminthiasis, and anthrax. Generally, flies have an affinity for lighter, darker colors, and flies like things that have used various baits with pungent odors. Therefore, this study used a yellow fly trap and used various baits with strong odors. This study aims to determine differences in the effectiveness of bait types in the use of yellow fly traps. This research is an experimental study with a quasi-experimental design. The research was carried out at a chicken farm located on Penangkaran Buaya street, Makroman Urban Village, Sambutan District, Samarinda City. Research in the field lasted for 4 days start at 08.00 – 12.00 WITA. The results showed that there were differences in the effectiveness of bait types in the use of yellow fly traps in chicken coops located on Penangkaran Buaya street, Makroman Village. There was a significant difference between shrimp bait - control (0.04 < 0.05), between squid bait - beef offal (0.016 < 0.05), between feed of beef offal - control 0.001 and between fish gills - control 0.02 < 0 ,05. The most effective in attracting flies was the bait of cow offal by an average of 47 flies per day. Controlling flies by using various baits on fly traps is quite easy, inexpensive, and, certainly, can be applied by the community. The control must be carried out especially for residential areas that are not far from the breeding sites of flies.